PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV B SD NEGERI 182 PEKANBARU - Raja Hamnorriza; Erlisnawati '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in the research was the students achievement in science still low with an average value 60,54 of the fourth graderes SDN 182 Pekanbaru. Among 46 students in class IV B, there were only 15 students (32,60%) who achieved above minimum completeness criteria (KKM), while 31 students (67,40%) still couldn’t achieve the minimum completenness criteria (KKM) by the minimum completeness criteria (KKM ) science subject is 70. The research is Classroom Action Research (CAR), wich aims to improve the science learning process of class IV B in year 2014/2015 which are consisted 46 students, with 24 boys and 22 girls. The research was conducted to 2 cycles. Each of first and second cycle were separated by three times meeting, which two times was the implementation of Contextual Teaching and Learning (CTL), and one was Test at the end of cycle. Before implementation Contextual Teaching and Learning (CTL) student achievement which was average 60,54. After implementation Contextual Teaching and Learning (CTL) student achievement improve 9,66% average to 70,20 at UHI, and improve 12,66% average to 73,20 at UH II. Based on the implementation of Contextual Teaching and Learning (CTL), so its learning model able to improve students achievement in science, it can be found that student achievement in science from pre Classroom Action Research (CAR) or before implementation Contextual Teaching and Learning (CTL) which was 60,54 average be improved 9,66% to 70,20 in first cycle, and be more improve 12,66% to 73,20 in second cycle. The percentage of teacher activities is also improve, it can be found that teacher activities in first cycle at first meeting is 75,00%, and be improved again at second meeting to 81,25% average. In second cycle at first meeting the teacher activities improve to 87,50%, and improve again to 93,75% average at second meeting. The percentage of students activities were also improve, it can be found that students activities in first cycle at first meeting is 81,25%, and be the same at second meeting by 81,25% average. In second cycle at first meeting the students activities had improving to 87,50%, and be improved again to 93,75% average at second meeting. Based on the result of the research, it can be concluded that the implementation of Contextual Teaching and Learning (CTL) can improve students achievement in science of class IV B SDN 182 Pekanbaru in year 2014/2015,Key Words : Contextual Teaching and Learning (CTL), Fourth Graderes Students Science Achievement.2